Knygos prekybos Lietuvos Didžiojoje Kunigaikštystėje XVIII amžiuje metmenys - Vladimirovas, Levas (Knygotyra, 1995)
The strengthening of the influence of the age of enlightenment has created in the Grand Duchy of Lithuania potential opportunities for the growth of interest for reading and books. But the complex and rather unfavourable political and economic conditions, the spreading anarchy in the country, leading gradually under pressure of external forces to the destruction of the Lithuanian statehood, and also a rather big percent of the illiteracy among the people, even among the gentry, and the severe censorship by the church, all this aggravated the normal development of the book trade and made this profession even rather risky. The progress of the book trade was also impeded by the bureaucratic pretensions of the guild of bookbinders in the city of Vilnius. This guild flatly asserted that dealing with books is a prerogative of its members. On the other hand, if the book publishing in Lithuania till the year 1773 was completely in the hands of monastic orders, in the professions of bookbinding and booktrade prevailed the private commercial initiative. The center of the book trade in the XVIII century was the capital of Lithuania Vilnius, where several bookshops have been established by local and foreign bookdealers. In the dealing with the local book production was the monopoly of the local bookdealers, the dealing with foreign book production was mostly in the hands of foreign individuals. Separately this paper deals with the experience in the book trade of the biggest local typographical enterprise – the printing shop of the Academy of Vilnius.